Building Site Adventure - Hayes, Susan, (Author at What on Earth Books (Firm); Rumiz, Susanna; Skipworth, Patrick (Tonbridge, Kent : What on Earth Books, 2021)
Pick up your toolbox and ride along with Maxie and all the construction vehicles to the building site. There's digging to do, pipes to lay, peek through pages and a pop-up surprise -- so put on your hard hat and get to work!
On board pages.
Keywords: Construction workers -- Juvenile fiction; Construction equipment -- Juvenile fiction; Board books; Pop-up books; Toy and movable books